Pemberdayaan Masyarakat melalui Diversifikasi Produk Olahan Pala (Myristica Fragrans) menjadi Kerupuk Kulit Pala - Lathifah, Suci Siti; Widiastuti , Diana; Aqilah , Siti; Amalia , Najla Nurul; Meyradhia, Azzura Gryniprillady (Yumary: Jurnal Pengabdian kepada Masyarakat, 2023)
Purpose: This study aimed to (1) empower the community in the Cita Tani Mandiri women's group by diversifying processed nutmeg products into nutmeg skin crackers. (2) Developing digital-based marketing for processed nutmeg products. Methodology: The implementation of community empowerment activities is carried out through two activities: training and mentoring, which is complemented by learning-by-doing techniques. Training activities were divided into (1) Survey of Partners' knowledge, (2) delivery of the theory of making crackers, and (3) demonstration and direct practice of making nutmeg leather crackers. Assistance activities include (1) assistance in making logos, brands, and product packaging; (2) assistance in marketing products using marketplaces; and (3) Monitoring and Evaluation. Results: The results obtained from this activity are: (1) increasing the skills of the members of the Cita Mandiri Farmers Group regarding the diversification of processed nutmeg products into nutmeg crackers; and (2) increasing the knowledge of the members of the Cita Mandiri Farmers Group regarding digital marketing strategies. Limitations: This activity was limited to processing and marketing nutmeg crackers. Contribution: This activity contributes to marketing management of processed nutmeg products.